Analisis strategi wisata alam curug lewi hejo menggunakan media sosial, menjadi “Analsis biblio matrik Wisata Alam di 2023” - Lasitang, Tabita Samaria; Anigomang, Ferdinand Romelus; Maruli, Elia; Awang, Mesak Yamres (Peneliti.net, 2023)
The aim of this research is to determine the influence of price, location and service quality at the Kalabahi New Business Shop, Alor Regency. This type of research is a quantitative description. Samples were taken using saturated sampling techniques. The sample in this study was 35 respondents. The data collection tools used were observation, interviews and literature study. The data analysis model used to answer the hypothesis is multiple analysis, t test, F test using SPSS version 22 for windows tools. This research instrument test is used to measure the level of validity, reliability and class assumptions of the answers to the research questionnaire. By using the SPSS version 22 For Windows calculation tool. Based on the validity test results for each variable with a Pearson correlation value ≥ 0.3, the validity test results for each variable are declared valid. The results of the reliability test for each variable with a Crobatc Alpha value ≥ 0.6 mean that the results of the reliability test for each variable are declared reliable. Kolmogrov - Smirnov Normality test results with sig value. ≥ 0.05 then the test results are declared normal. The results of the heteroscedasticity test show that the value of each independent variable is > 0.05, so there is no heteroscedasticity in this research. The results of the multicollinearity test show that the VIF value > tolerance, so this research did not occur multicollinearity. The results of the linearity test between the dependent variable and the independent variable show that the deviation from linearity value is > 0.05, so there is a relationship between the dependent variable and the independent variable. The analytical method used is multiple linear regression analysis technique. The results using the t test answered the first, second and third hypotheses, while multiple linear regression analysis simultaneously used the F test to determine the fourth hypothesis, namely to determine the influence of price, location and service quality on buyers' decisions at the new business store in Kalabahi, Alor Regency. Based on the results of partial and simultaneous multiple linear regression analysis calculations, the significance value of the Individual Characteristics variable is 0.000, the Work Motivation variable is 0.003, the communication variable is 0.004, and the simultaneous influence value of the F test significance is 0.000b, the results of the t test and the F test is smaller than alpha (0.05), then the hypothesis testing proposed in this research is as follows: there is an influence of price, location and service quality on buyers' decisions at the Kalabahi New Business Shop, Alor Regency.